Quicksand: America's pursuit of power in the Middle East - Wawro, Geoffrey (New York, 2010)
In this definitive and revelatory work, noted historian Geoffrey Wawro approaches America's role in the Middle East in a fundamentally new way-by encompassing the last century of the entire region rather than focusing narrowly on a particular country or era. With verve and authority, he offers piercing analysis of the region's iconic events over the past one hundred years-from the birth of Israel to the rise of Al Qaeda. Throughout, he draws telling parallels between America's past mistakes and its current dilemmas, proving that we're in today's muddle not just because of our old errors but because we keep repeating those errors.
Keywords: United States-Foreign relations-Middle East